2022
DOI: 10.21608/ejhc.2022.254054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foot Massage on Pain and Anxiety Levels among Patients underwent Laparoscopic Cholecystectomy

Abstract: Background: Insufficient pain treatment in the early stages after laparoscopic cholecystectomy may cause patients to breathe shallowly and quickly because they are afraid of experiencing pain. Pharmacologic and nonpharmacologic complementary therapies such as foot massage can be used to manage pain and anxiety after laparoscopic cholecystectomy. Aim: To determine effect of foot massage on pain and anxiety levels among patients who underwent laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…In addition, foot massage was found to substantially reduce the anxiety levels after laparoscopic cholecystectomy 20. We should also consider several limitations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, foot massage was found to substantially reduce the anxiety levels after laparoscopic cholecystectomy 20. We should also consider several limitations.…”
Section: Discussionmentioning
confidence: 94%
“…91 publications were identified through the initial search of databases, and five RCTs were ultimately included in the metaanalysis. 14,15,[20][21][22] The baseline characteristics of 5 eligible RCTs were summarized in Table 1. The 5 studies were published between 2018 and 2022, and total sample size was 546.…”
Section: Literature Search Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Among the six RCTs, five studies reported pain scores at 10–30 min 12 21 26 30 34 , three studies reported pain scores at 60 min 21 22 34 , two studies reported pain scores at 90 min and pain scores at 120–150 min 26 34 , and two studies reported additional analgesia 26 34 . Jadad scores of the six included studies varied from three to four, and thus all studies were considered to have high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, foot massage and hand massage were both included in this meta-analysis. Five studies reported the foot massage 12 21 22 26 34 , while two studies reported the hand massage 26 30 . Secondly, the detail procedures of massage intervention were not completely same in one massage method, which may affect the efficacy assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation